Optimalisasi Penggunaan Digital Marketing Dalam Meningkatkan Penjualan UMKM Binaan Di Kelurahan Sananwetan - Gideon Setyo Budi Witjaksono; Adella Ratna Nur Dianti; Arde Agung Hidayatulloh; Dian Aviyanti Putri; Ellyn Dya Lestari; Shafira Salsabilla (Jurnal Pengabdian Masyarakat Nusantara, 2023)
According to Law No. 20 of 2008, Micro, Small, and Medium Enterprises (MSMEs) are defined as independent business activities carried out by individuals or groups that are not branches of larger companies. MSMEs plays a significant role as an economic driver in Indonesia and can absorb up to 97% of the workforce. The city of Blitar has a total of 9,243 MSMEs units producing 14,000 types of products. One of the challenges faced by MSMEs is the underutilization of social media as a marketing platform. Digital marketing is considered a more effective and efficient communication medium for product promotion. By implementing digital marketing strategies, MSMEs can improve their marketing systems, expand their target market reach, and enhance sales activities for the future. Therefore, to help address the challenges faced by MSMEs, a socialization program is conducted to provide guidance on the initial steps to gain publicity on social media.